Two-dimensional cyano-bridged coordination polymer of Mn(H2O)2[Ni(CN)4]: structural analysis and proton conductivity measurements upon dehydration and rehydration. Issue 42 (10th October 2018) - Alowasheeir, Azhar; Tominaka, Satoshi; Ide, Yusuke; Yamauchi, Yusuke; Matsushita, Yoshitaka
Abstract : The interlayer spaces in the two-dimensional cyano-bridged coordination polymer were found to be non-ionic and not proton conductive. Abstract : Two-dimensional (2D) materials are widely investigated as electronic or catalytic materials as well as being conventionally used as adsorbents for accommodating guest molecules in the interlayer spaces. 2D coordination polymers have flexible structures, which are transformed even by a weak external stimulus such as a humidity change. Here we report a structural analysis and proton conductivity measurements of a 2D cyano-bridged coordination polymer of the Mn[Ni(CN)4 ] system upon dehydration and rehydration. The structure of the sample at high humidity was determined by single-crystal diffraction, while the structure at low humidity was solved by Rietveld analysis of synchrotron powder diffraction data. At high humidity, the material contains coordinated and non-coordinated water molecules as [Mn(H2 O)2 Ni(CN)4 ]·3H2 O. These water molecules were further analyzed by TG-DTA and classified into three types: (i) two coordinated molecules, (ii) two weakly adsorbed non-coordinated molecules and (iii) a strongly adsorbed non-coordinated molecule. These water molecules play a key role in crystal structure transformation upon dehydration/hydration, where the two-dimensional coordination network is retained but the curvature changes by tilting of MnO6 octahedra owing to the change in hydrogen bonds between the water molecules. Because the water molecules form hydrogen bonding networks, proton conductivity was expected. Thus, we investigated the proton conductivity using the single-crystal AC impedance method and found that the crystals were insulating. This in turn suggests that the water molecules in the interlayer spaces do not dissociate into protons mostly, and the spaces are non-ionic.